2013
DOI: 10.1097/phm.0b013e318282c9f2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pain Score Reduction Using Triamcinolone vs. Dexamethasone in Cervical Transforaminal Epidural Steroid Injections

Abstract: The mean reduction in pain score in this set of 441 patients with cervical radiculopathy treated with transforaminal epidural steroid injections was independent of the type of corticosteroid formulation used. Triamcinolone (40 mg) and dexamethasone (15 mg) produced similar benefits as measured by the patients' self-reported pain scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 13 publications
2
31
0
Order By: Relevance
“…However, n=7 (17 %) patients of the dexamethasone group needed three injections compared to only n=1 (3 %) patient of the triamcinolone group, which was the only statistically significant finding in the Kennedy et al study [57]. Patient outcome after cervical transforaminal epidural steroid injection revealed similar findings compared to lumbar injections: particulate steroids did not demonstrate a superior effectiveness compared to non-particulate steroids [58,59]. Finally, it might be noted, that a prospective, randomized, double-blind, dose-response study on lumbar transforaminal epidural injections did not find a statistical difference in efficacy for dexamethasone dosage of 4 mg compared with 8 or 12 mg over a 12-week period [60].…”
Section: Efficacy Of Various Steroids In Lumbar Epidural Injectionssupporting
confidence: 67%
“…However, n=7 (17 %) patients of the dexamethasone group needed three injections compared to only n=1 (3 %) patient of the triamcinolone group, which was the only statistically significant finding in the Kennedy et al study [57]. Patient outcome after cervical transforaminal epidural steroid injection revealed similar findings compared to lumbar injections: particulate steroids did not demonstrate a superior effectiveness compared to non-particulate steroids [58,59]. Finally, it might be noted, that a prospective, randomized, double-blind, dose-response study on lumbar transforaminal epidural injections did not find a statistical difference in efficacy for dexamethasone dosage of 4 mg compared with 8 or 12 mg over a 12-week period [60].…”
Section: Efficacy Of Various Steroids In Lumbar Epidural Injectionssupporting
confidence: 67%
“…The only statistically significant finding in this study was that a greater percentage of subjects that received (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Range (1-20) Mean pain (0-10) 6.3 6.5 0.599 Range (4)(5)(6)(7)(8)(9)(10) Range ( dexamethasone underwent three injections. Although it affected only a small number of subjects, this could be due to a large number of reasons.…”
Section: Discussionmentioning
confidence: 89%
“…Others have questioned its efficacy due to the soluble nature of the nonparticulate corticosteroids [16]. Several studies have assessed the comparative effectiveness of different corticosteroid agents for cervical radicular pain, including one prospective study by Dreyfuss et al [17] and two small retrospective studies by Lee et al [18], and Shakir et al [19]. Both retrospective studies showed similar effectiveness between dexamethasone and triamcinolone in cervical TFESIs, with no statistical difference in self-reported patient pain scores.…”
Section: Introductionmentioning
confidence: 95%
“…127 In the 3 retrospective studies, one found depot steroids was statistically better than nonYdepo-steroids, 128 one showed a trend toward superiority for depo-steroids over non-depot steroids in patients with cervical radiculopathy, 105 and another found no difference between depo-and nonYdepo-steroids for cervical TF ESI. 129 In summary, there is conflicting evidence with a low degree of certainty that depo-steroids provide superior relief compared with nondepot steroids. 2…”
Section: Effect Of Type Of Steroidmentioning
confidence: 99%